Alginate incorporated multi-walled carbon nanotube as new sorbent for selective extraction of non-steroidal anti-inflammatory drugs / Nurzaimah Zaini @ Othman - Zaini @ Othman, Nurzaimah (2019)
Alginate incorporated multi-walled carbon nanotubes (Alg-MWCNT) was utilized as sorbent in dispersive micro solid phase extraction (D-μ-SPE) and online solid phase extraction (online-SPE) for the extraction of non-steroidal anti-inflammatory drugs (NSAIDs) in water samples prior to high performance liquid chromatography (HPLC) analysis. Selected commonly used NSAIDs namely salicylic acid (SAL), naproxen (NAP), diclofenac (DIC), ibuprofen (IBU) and mefenamic acid (MEF) were used as target analytes.